Determination of Characteristics of the Torch Discharge Plasma Burning in a Mixture of Atomic and Molecular Gases - Lucenko (Lutsenko) Yu. Yu. Yuri Yurievich (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen